Retirement: Keeping the Zeal for Teaching Aflame - Parinas, Sherwin M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This phenomenological inquiry intended to unearth the lived experiences of the retired faculty members on post retirement career. Previous studies had linked retirement with leisure, relaxation and benefit. However, this current study viewed it as an avenue to pursue a career as evidenced by twenty-one (21) retired teachers from basic to tertiary education in both public and private institutions. The salient findings revealed that the preference to work after tenure was anchored from economic reasons, defying age, loss and fear of insignificance. As they were nearing the twilight, working for them meant making every tick count. Economic reason was also a factor as they found their pension too minimal an amount to purchase not only basic commodities but hospitalization and maintenance medicine as years went by. But seasoned as they were, they managed to jump over the hurdles by being optimistic and maintaining circle as support system like family and friends, above all, imploring the Divine Providence. To lighten the plight, it was suggested that institutions may implement policies like seminars and training that could provide a better retirement preparation and transition to probable retirees.